2015
DOI: 10.3171/2015.8.focus15324
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal and cerebellar atrophy in patients with Cushing’s disease

Abstract: OBJECT Cushing’s disease (CD) may cause atrophy of different regions of the human brain, mostly affecting the hippocampus and the cerebellum. This study evaluates the use of 3-T MRI of newly diagnosed patients with CD to detect atrophic degeneration with voxel-based volumetry. METHODS Subjects with newly diagnosed, untreated CD were included and underwent 3-T MRI. Images were analyzed using a voxelwise s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 38 publications
(42 reference statements)
4
20
0
Order By: Relevance
“…The mean and standard deviation of serum cortisol levels were 32.34 ± 46.50 ng/mL (range = 7.95–305.77 ng/mL) in our samples, which is similar to the plasma cortisol levels reported in 95 healthy elderly men at 9 am (range = 38.48–329.10 ng/mL, age range 65–70 years old, MacLullich et al, 2005), and is much lower than the levels in Cushing’s disease patients (range = 147.05–829.31 ng/mL, Burkhardt et al, 2015). Details of the demographic data are reported in Table 1.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The mean and standard deviation of serum cortisol levels were 32.34 ± 46.50 ng/mL (range = 7.95–305.77 ng/mL) in our samples, which is similar to the plasma cortisol levels reported in 95 healthy elderly men at 9 am (range = 38.48–329.10 ng/mL, age range 65–70 years old, MacLullich et al, 2005), and is much lower than the levels in Cushing’s disease patients (range = 147.05–829.31 ng/mL, Burkhardt et al, 2015). Details of the demographic data are reported in Table 1.…”
Section: Resultssupporting
confidence: 86%
“…For instance, brain atrophy in bilateral hippocampal and cerebellar gray matter (GM) expressing high levels of glucocorticoid receptors (de Kloet et al, 2005; Hawrylycz et al, 2012) was observed in patients with uncontrolled Cushing’s disease, a state with high cortisol levels in the blood (Burkhardt et al, 2015). A recent meta-analysis showed that the damaging effect of high cortisol levels in Cushing’s syndrome on the human brain was irreversible (Andela et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, for the hippocampus a 10% increase has been demonstrated after disease remission [32]. Similar results have been found for the cerebellum, where smaller grey matter volumes were found in active patients compared to controls but did not differ when comparing with patients in remission [9, 13, 33]. …”
Section: Discussionsupporting
confidence: 66%
“…However, these studies did not include segmentation of the white and grey matter. Accessing modern and more sophisticated analytical tools, three volumetric MR studies have yielded inconsistent results . Resmini et al …”
Section: Discussionsupporting
confidence: 60%
“…Accessing modern and more sophisticated analytical tools, three volumetric MR studies have yielded inconsistent results. 8,30,31 Resmini et al 30 found no differences in hippocampal volume between patients with active CS and HC, Andela et al 8 did not find alterations in the grey matter of hippocampus in patients with long-term remission CD. Two diffusion tensor-imaging studies demonstrated widespread reductions of white matter integrity in patients with CD.…”
Section: Discussionmentioning
confidence: 98%